Outcomes, Healthcare Resource Utilization, and Costs of Overall, Community-Acquired, and Hospital-Acquired Acute Kidney Injury in COVID-19 Patients - Jay L. Koyner; Rachel H. Mackey; Ning A. Rosenthal; Leslie A. Carabuena; J. Patrick Kampf; Paul McPherson; Toni Rodriguez; Aarti Sanghani; Julien Textoris (Journal of Health Economics and Outcomes Research, 2023)
# Background In hospitalized patients with COVID-19, acute kidney injury (AKI) is associated with higher mortality, but data are lacking on healthcare resource utilization (HRU) and costs related to AKI, community-acquired AKI (CA-AKI), and hospital-acquired AKI (HA-AKI).